Association of Hand Stiffness with Balance Impairment in Chronic Stroke Patients - Shafuq Shahid, Zeest Hashmi, Hira Rehman, Saima Riaz, Muhammad Sulman, Rehan Ramzan Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the association of hand stiffness with balance impairment in chronic stroke patients. Methodology: A cross sectional study was conducted on eighteen chronic stroke patients with age range between 40 to 70 years. Patients were taken from Riphah Rehab Center and Govt. Kot Khawaja Saeed Teaching Hospital KEMU Lahore. The balance of patients was assessed by using Berg Balance Scale (BBS) and Timed Up and Go Test (TUG) while motor function of the hand was assessed by using Fugl Meyer Assessment-Upper Extremity (FMA-UE). Results: The analysis of data done by using SPSS version25. The mean value of age of the patients was 54.9 + 9.09 years. FMA-UE tool was used to assess motor activity of hand. Postural balance was measured by using BBS and TUG. The results showed a positive correlation of FMA-UE with BBS (rs = 0.704, p =<0 .001) and a negative correlation with TUG (rs = -.705, p = .001). Conclusion: This study concluded that there is association of hand stiffness with balance impairment in chronic stroke patients